2019
DOI: 10.3390/pr7010047
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Preparation and Hydration Properties of a New Cementitious Material for Tailings Discharge

Abstract: Blast furnace slag (BFS) is often used as a cement-based raw material for underground filling and surface cemented paste discharge of tailings during mining processes. This paper studied a new cement-based material (NCM) with BFS to replace ordinary Portland cement (OPC). A uniaxial compressive strength (UCS) experiment was used to test the mechanical strength of samples; X-ray diffraction and thermal gravity experiments were used to test the crystalline phases and amount of hydration products by samples; a sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Previous works have been studied the phase composition of the OPC hydration products [16,22,28,29]. e erefore, XRD analysis is not carried out for samples of the OPC-CTB and OPC paste.…”
Section: E Crystalline Phases Of Hydrationmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous works have been studied the phase composition of the OPC hydration products [16,22,28,29]. e erefore, XRD analysis is not carried out for samples of the OPC-CTB and OPC paste.…”
Section: E Crystalline Phases Of Hydrationmentioning
confidence: 99%
“…TG/DTG experiments were performed on prepared OPC-CTB samples to test the weight losses of the hydration products. For OPC paste, a scholar conducted a thermal analyses experiment and found that its hydration products include C-S-H, Ca(OH) 2 , and CaCO 3 [16]. erefore, the TG/DTG curve of OPC paste is not listed in this paper.…”
Section: E Weight Losses Of Hydration Products Of Opc-mentioning
confidence: 99%
See 2 more Smart Citations
“…Hou, Y. et al, Study on the Preparation and Hydration Properties of a New Cementitious Material for Tailings Discharge[64].…”
mentioning
confidence: 99%